1998
DOI: 10.1148/radiology.208.3.9722841
|View full text |Cite
|
Sign up to set email alerts
|

Hypoechoic plaque at US of the carotid artery: an independent risk factor for incident stroke in adults aged 65 years or older. Cardiovascular Health Study.

Abstract: In asymptomatic adults aged 65 years or older, that risk of incident stroke was associated with two US features: hypoechoic internal carotid arterial plaque and an estimated internal carotid arterial stenosis of 50%-100%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
230
1
13

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(250 citation statements)
references
References 0 publications
6
230
1
13
Order By: Relevance
“…We adopted the same ultrasonography protocol used in one of the largest population-based studies of carotid atherosclerosis among elderly Americans [the Cardiovascular Health Study (CHS)]. 2,5 A single trained physician (A.K.) conducted the ultrasonographic scanning and interpreted the results.…”
Section: Baseline Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…We adopted the same ultrasonography protocol used in one of the largest population-based studies of carotid atherosclerosis among elderly Americans [the Cardiovascular Health Study (CHS)]. 2,5 A single trained physician (A.K.) conducted the ultrasonographic scanning and interpreted the results.…”
Section: Baseline Examinationmentioning
confidence: 99%
“…[1][2][3][4] Furthermore, 2 prospective studies have investigated the association between echogenicity of plaques or carotid artery lesions and stroke risk in American populations; 1 study indicated that hypoechoic plaque was associated with increased risk of ischemic stroke, 5 and the other study implied that acoustic shadowing on carotid artery lesions is predictive of ischemic stroke. 6 In Asian countries, a previous follow-up study of Japanese patients with cardiovascular diseases or high-risk profiles showed a positive association between the severity of carotid plaque and the risk of ischemic stroke, 7 but no prospective study has been conducted in a general population.…”
mentioning
confidence: 99%
“…Recent population-based studies have indicated that soft stenotic plaques harbor a higher risk of clinical cerebrovascular disease than hard stenotic plaques. 15,16 Whether these morphological structures could be related to metabolic changes reflected by HbA 1c levels has not been examined previously.…”
mentioning
confidence: 99%
“…Recent evidence, however, suggests that plaque composition, rather than its hemodynamic effect, is a better predictor of outcome (1). Specifically, a thin or ruptured fibrous cap and a large lipid core seem to relate to risk of stroke (2,3). Previous work has shown that MRI can characterize the composition of human atherosclerotic plaques both ex vivo (4 -6) and in vivo (7,8).…”
mentioning
confidence: 99%